Flavors of obligation: the syntax/semantics of deontic deve in Brazilian Portuguese - de Oliveira, Roberta Pires; Rech, Núbia Ferreira (Letras de Hoje, 2016)
In this paper we propose a theoretical description of the results of an experiment of interpretation. The experiment shows that the participants attribute different deontic interpretations – “ought to be” and “ought to do” – depending on the argument structure projected by the verb. This result adds another contrast between epistemic and deontic modals. Theoretically, although we assume Hacquard’s (2006, 2010) proposal, we show that it cannot account for the “ought to be” interpretation. We argue that the deontic reading is possible when a modal is relative to an event with an agentive participant provided by the ordering source. This activates in ModP an accessory projection for checking the +Ag feature. Hence the deontic is always interpreted as “ought to be” with unaccusatives, and with unergatives and transitives the deontic can be interpreted also as “ought to do” when their external argument is agentive, because it can check the +Ag feature. ******************************************************************** Matizes de obrigação: a sintaxe e a semântica do deôntico deve no português brasileiro Resumo: Neste artigo, propomos uma descrição teórica dos resultados de um experimento de interpretação. Este mostra que os participantes atribuem diferentes interpretações deônticas – “ought to be” e “ought to do” – dependendo da estrutura argumental projetada pelo verbo. Os resultados do experimento apontam mais um contraste entre epistêmicos e deônticos. Teoricamente, assumimos a proposta da Hacquard (2006, 2010), mas mostramos que ela não dá conta da interpretação “ought to be”. Argumentamos que a interpretação deôntica é possível quando um modal é relativo a um evento com um participante agentivo, fornecido pela fonte de ordenação. Então, será ativada em ModP uma projeção acessória para checar o traço +Ag. Por essa razão, o deôntico é sempre interpretado como “ought to be” com inacusativos; já com inergativos e transitivos, o deôntico pode ser interpretado também como “ought to do” quando o argumento externo for um agente, porque ele poderá checar o traço +Ag. Palavras-chave: Interface sintaxe/semântica; Deônticos; Experimento; Modalidade; Português brasileiro